Facile Fabrication of Graphene‐Containing Foam as a High‐Performance Anode for Microbial Fuel Cells. Issue 30 (19th June 2015) - Yang, Lu; Wang, Shuqin; Peng, Shuqin; Jiang, Hongmei; Zhang, Youming; Deng, Wenfang; Tan, Yueming; Ma, Ming; Xie, Qingji
Abstract Facile fabrication of novel three‐dimensional anode materials to increase the bacterial loading capacity and improve substrate transport in microbial fuel cells (MFCs) is of great interest and importance. Herein, a novel graphene‐containing foam (GCF) was fabricated easily by freeze‐drying and pyrolysis of a graphene oxide–agarose gel. Owing to the involvement of graphene and stainless‐steel mesh in the GCF, the GCF shows high electrical conductivity, enabling the GCF to be a conductive electrode for MFC applications. With the aid of agarose, the GCF electrode possesses a supermacroporous structure with pore sizes ranging from 100–200 μm and a high surface area, which greatly increase the bacterial loading capacity. Cell viability measurements indicate that the GCF possesses excellent biocompatibility. The MFC, equipped with a 0.4 mm‐thick GCF anode, shows a maximum area power density of 786 mW m−2, which is 4.1 times that of a MFC equipped with a commercial carbon cloth anode. The simple fabrication route in combination with the outstanding electrochemical performance of the GCF indicates a promising anode for MFC applications.